Renal extracellular vesicles: from physiology to clinical application. (27th May 2016) - Morrison, E. E.; Bailey, M. A.; Dear, J. W.
Abstract : Extracellular vesicle biogenesis and interaction with recipient cells. Exosomes are generally considered a homogeneous population of vesicles, derived from the endosomal pathway. This process commences with the invagination of the plasma membrane and terminates when the mature multivesicular body (MVB) fuses with the limiting aspect of the plasma membrane. The contents of the MVB are liberated into the extracellular environment, releasing exosomes. Microvesicles are formed by the budding of the plasma membrane, releasing a heterogeneous population of larger vesicles. Due to their biogenesis, EVs (pink) act as vectors for mRNA, microRNA (miRNA), protein, dsDNA, mitoDNA and antigens. This parcel of biological information can be interrogated as a biomarker reservoir or propagate a signal to a recipient cell. EV interaction with a recipient cell has been described through a number of modalities, ultimately influencing a recipient cell's proteome and function. The contents can be delivered directly to the cytosol by fusion with the recipient cell membrane or through phagocytosis, macropinocytosis or clathrin‐mediated endocytosis. Alternatively, the vesicles can signal by directly activating cell surface receptors via ligands or present antigen and MHC. Abstract: Urinary extracellular vesicles (uEVs) are released from all regions of the kidney's nephron and from other cells that line the urinary tract. Extracellular vesicles retain proteomic and transcriptomic markers specific to their cell of origin and so represent a potential reservoir for kidney disease biomarker discovery. Exosomes, a subtype of uEVs, are distinguished from other vesicles by features related to their biogenesis within cells: mature multi‐vesicular bodies fuse with the cellular membrane to liberate exosomes into the extracellular space. uEVs represent a novel cell signalling mechanism because they can be shuttled to a recipient cell and, through a number of proposed mechanisms, affect the recipient cell's proteome and function. Here we review the current evidence for uEV signalling along the nephron, their role in health and disease of the kidney, and their potential for clinical translation as biomarkers and therapeutics.